Early (6 months) results of a pilot prospective study to investigate the efficacy and safety of sirolimus coated balloon angioplasty for dysfunctional arterio-venous fistulas: MAgicTouch Intervention Leap for Dialysis Access (MATILDA) Trial. - Tjun Y Tang; Shereen X Y Soon; Charyl J Q Yap; Sze Ling Chan; Ru Yu Tan; Suh Chien Pang; Shaun Q W Lee; Hao Yun Yap; Edward T C Choke; Chieh Suai Tan; Tze Tec Chong (PLoS ONE, 2020)
Background The aim of this pilot study was to evaluate the safety and efficacy of the MagicTouch™ sirolimus-coated balloon (SCB) catheter (Concept Medical Inc., Tampa, FL, US) on improving the patency of failing arterio-venous fistulas (AVF) with de novo and recurrent stenoses. MATILDA reports early outcomes at 3- and 6 months post intervention. Methods Single-centre, single-arm prospective pilot study of 33 (18 males; mean age 64.7±11.6 years) end-stage renal failure Asian patients with a dysfunctional AVF, who underwent SCB angioplasty between May 2019-January 2020. All procedures were performed under local anaesthetic without sedation and as day surgery. All patients were prescribed dual antiplatelet therapy for 3 months and followed up with Duplex ultrasound at 3 and 6 months. Results 47 stenotic target lesions treated and 24/33 (72.7%) patients were for restenosis. Main indications for intervention was low/dropping access flow (21/33; 63.6%) and most common target lesion was in the juxta-anastomosis (19/47; 40.4%). There was 100% technical and procedural success. There were no peri-procedural complications related to the SCB. The target lesion primary patency rates at 3 and 6 months were 46/47 (97.9%) and 29/35 (82.9%) respectively. Circuit access patency rates at 3 and 6 months were 31/33 (93.9%) and 17/25 (68%) respectively. There was one (2.9%) death at 6 months and 4/33 (12.1%) overall to date, all from patients' underlying co-morbidities. Conclusions SCB angioplasty for dysfunctional AVF circuits is a safe and efficacious modality in Asian haemodialysis patients at six months comparable if not better than the paclitaxel data reported to date in the literature.